PENGARUH MEDIA PEMBELAJARAN KARTU BERGAMBAR TERHADAP HASIL BELAJAR SUBTEMA ORGAN GERAK HEWAN - Lina Novita; Raden Teti Rostikawati; Karina Aulia Fitriani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
This research is a type of quantitative research with a quasi experimental approach which consists of pictorial card media as independent variables and learning outcomes as dependent variables. The purpose of this study for to determine whether there is an influence on the learning outcomes of animal motion organ subthemes through the learning media of illustrated cards. This research uses a quasi experimental method. This research was conducted at Karadenan Kaum State Elementary School in Bogor Regency in the class VA and VB Even Semester of the 2019/2020 Academic Year. The analysis technique used is the prerequisite test data analysis which includes data error normality test, homogeneity variance test, then hypothesis testing using t test. Based on the results of data analysis the learning outcomes obtained through the Learning Card Picture Media with an N-Gain value of 74.62. with 100 percent mastery learning outcomes and without pictorial card learning media obtained an N-Gain score of 62.86 with 75 percent mastery learning outcomes. The results of hypothesis testing stated H0 was rejected and Ha was accepted because tcount (3.2036) greater than ttable (1.99346). Based on the results of the above research, it can be concluded that, there is an influence on the learning outcomes of animal motion organ subthemes through the media of learning cards. The most effective learning media on animal motion organ subthemes is the Picture Card Learning media.